Application of Augmented Reality (Ar) Technology in PAI Learning on Islamic History to Improve Student Learning Outcomes at SMPN 01 Pamekasan - Qonita Alfiya Khoirunnisa; Muliatul Maghfiroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to improve student learning outcomes in Islamic history using Augmented Reality (AR) technology. This study is a Classroom Action Research (CAR) model using the Kemmis and McTaggart model and was conducted with 32 students in grade XI at SMPN 01 Pamekasan. The study was conducted in two cycles. At the beginning of the meeting, a pre-test was administered to determine students' initial abilities, then at the end of each cycle, a post-test was administered to measure student understanding. Data collection techniques included learning achievement tests, observations, interviews, tests, and documentation. Data were analyzed descriptively using qualitative and quantitative methods. Indicators of success in this study were an increase in learning outcomes for each student by 10 points and a percentage of all students completing the learning achievement score of 80%. Before implementing augmented reality, student learning outcomes in the pre-action phase were 15%. After implementing augmented reality in cycle I, this increased to 63% of students completing the learning achievement. Meanwhile, in cycle II, student understanding increased further to 91%